Trade behaviour and transactions costs in live animal marketing in Ethiopian highland markets - Jabbar, M.A.; Benin, Samuel (International Food Policy Research Institute, 2005)
A survey of 131 livestock traders in 38 markets in the highlands of Ethiopia provided information on trader behaviour and transactions costs. The livestock market is characterized by non-standardized products and lack of information in the public domain about supply, demand and prices. Consequently, livestock trading is largely a personalized business though intermediaries, especially brokers, are used for trading in distant markets. Most traders use their own capital as access to credit, especially formal credit, is very limited. Estimated costs and margins of case transactions show low returns and losses on traders' capital in some cases. Analysis of the structure of variable costs show that most are physical marketing costs. Transactions costs are smaller as most exchanges are conducted in the physical presence of the parties. Unstable price, multiple taxes, non-transparent tax system, limited access to credit and weak demand for the products traded are perceived as major problems of marketing. All the problems are amenable to public policy for improving the market environment and marketing efficiency.